Prospects for Derivatives of Game Animals - Elena A. Vechtomova; Irina K. Kuprina; Maria M. Orlova; Timothy A. Larichev (Техника и технология пищевых производств)
Game animals are a source of biologically active substances that requires a strict resource and biodiversity control. The research objective was to analyze three years of supply, demand, export, and import for brown bear, deer, and musk deer by-products. The review featured Russian and foreign articles on game animals published in 2016–2020, as well as customs information on imports and exports for this raw material. The research methods included systematization, analysis, and description. The population of brown bears in the Russian Federation is constantly growing. In 2018, it increased by 4% compared to 2017. Bear derivatives are in high demand in China, Italy, France, etc. The total number of importers in 2019 exceeded 25. In 2017, deer products were the most popular game derivatives exported from Russia to 35 countries. The biggest importer is China. In 2018, the volume of exports of deer and musk deer derivatives maintained the same value, but the list of importers changed. In 2019, the export volume increased by 1.4 times, and the number of importing countries reached 50. Russia is the leading exporter and importer of raw materials and derivatives from brown bears, deer, and musk deer. The market for game derivatives is actively developing. An increase in the number of predatory game animals, e.g., the brown bear, may adversely affect the local ecosystems, which can be prevented by licensed hunting. The high content of biologically active substances makes it possible to use game raw materials for new functional products.